Neuro-Developmental follow up of high-risk newborns using hammersmith-dubowitz method - Dr. Lakshmi Priya Chadalawada; Dr. Nalluru Lakshmi Sravanthi; Dr.Vijayalakshmi Bhimireddy; Dr. Kantakumari Pinnamaneni (Pediatric Review: International Journal of Pediatric Research, 2019)
Background and Objectives: High risk infants are prone to delay in neurological development due to perinatal damage sustained by the brain and nervous tissue. Despite being on regular follow-up, delayed neurological development is often missed even by experienced examiners as most of the examination and history are subjective. We aim to validate an objective scoring system- the Hammersmith-Dubowitz neurological exam which was extensively researched and developed taking into consideration normal responses from a normal cohort.Materials and Methods: Over a period of two years, 112 infants were categorized as high-risk newborns and were followed up for a period of one year of age.The children underwent detailed milestone assessment, physical and neurological examination by two independent examiners along with objective scoring with Hammersmith infant neurological exam. Any abnormality in these tests was considered delayed development.Results: Of the 112 infants, 102 came for at least one follow up and 81 completed one year follow up with a mean follow up duration of 9.42 months. On the combined assessment scale of developmental, physical and complete neurological examination 7.84% infants were found to be abnormal. However, on objective assessment with Hammersmith neurological examination 16.67 % of the infants were found to have abnormal neurological development.Conclusion: Hammersmith neurological examination is a useful objective scoring tool to identify delayed neurological development early.